PENGARUH SERVICESCAPE TERHADAP BEHAVIORAL INTENTION DI KAFE KUPU-KUPU (Survei Terhadap Tamu Yang Melakukan Pembelian di Kafe Kupu-Kupu) - Statifiansyah, Friga; Siswhara, Gita (THE Journal : Tourism and Hospitality Essentials Journal, 2016)
This aims to find the influence of service scape to the behavioral intention for visitors at the restaurant. Many researchers have already discovered that people dine in the restaurant, not just because of the food taste, but also the ambience or physical attributes. Many restaurants have attempted to design its service scape to create a competitive advantage for surpassing the competitors. The variables studied in this research are service scape, as the independent variable, and the behavioral intention as the dependent one. The dimension of service scape consists of the ambient conditions, spatial layout, sign and symbols. Whereas, the dimension of behavioral intention consists of repurchase intention and the tendency of spreading the word-of-mouth about the restaurant. The instrument of this research was questionnaires that are distributed to 100 respondents. The multiple regression's statistical tool was used for analyzing the data and assisted by SPSS 18. The result indicated that the sign and symbol had the highest impact to the behavioral intention.